The StbHLH47 transcription factor negatively regulates drought tolerance in potato (Solanum tuberosum L.) - Peijie Wang; Xiaojuan Wu; Nan Li; Hushuai Nie; Yu Ma; Juan Wu; Zhicheng Zhang; Yanhong Ma (BMC Plant Biology)
Abstract Background Drought stress is a major environmental constraint affecting crop yields. Plants in agricultural and natural environments have developed various mechanisms to cope with drought stress. Identifying genes associated with drought stress tolerance in potato and elucidating their regulatory mechanisms is crucial for the breeding of new potato germplasms. The bHLH transcription factors involved play crucial roles not only in plant development and growth but also in responsesresponse to abiotic stress. Results In this study, the StbHLH47 gene, which is highly expressed in potato leaves, was cloned and isolated. Subcellular localization assays revealed that the gene StbHLH47 performs transcriptional functions in the nucleus, as evidenced by increased malondialdehyde (MDA) content and relative conductivity under drought stress. These findings indicate that overexpressing plants are more sensitive to drought stress. Differential gene expression analysis of wild-type plants (WT) and plants overexpressing StbHLH47 (OE-StbHLH47) under drought stress revealed that the significantly differentially expressed genes were enriched in metabolic pathways, biosynthesis of various plant secondary metabolites, biosynthesis of metabolites, plant hormone signal transduction, mitogen-activated protein kinase (MAPK) signalling pathway-plant, phenylpropanoid biosynthesis, and plant‒pathogen interactions. Among these pathways, the phenylalanine and abscisic acid (ABA) signal transduction pathways were enriched in a greater number of differentially expressed genes, and the expression trends of these differentially expressed genes (DEGs) were significantly different between WT and OE-StbHLH47. Therefore, it is speculated that StbHLH47 may regulate drought resistance mainly through these two pathways. Additionally, RT‒qPCR was used for fluorescence quantification of the expression of StNCED1 and StERD11, which are known for their drought resistance, and the results revealed that the expression levels were much lower in OE-StbHLH47 than in WT plants. Conclusion RNA-seq, RT‒qPCR, and physiological index analyses under drought conditions revealed that overexpression of the StbHLH47 gene increased the sensitivity of potato plants to drought stress, indicating that StbHLH47 negatively regulates drought tolerance in potato plants. In summary, our results indicate that StbHLH47 is a negative regulator of drought tolerance and provide a theoretical basis for further studies on the molecular mechanism involved.